OPTIMASI IMPLEMENTASI SOFT SKILL BERBASIS TEKNOLOGI INFORMASI DALAM AKADEMIK PENDIDIKAN DI SEKOLAH KEJURUAN - Amrizal Amrizal; Rika Harman; Syahril Effendi; Sasa Ani Arnomo (LPPM Universitas Putera Batam, 2022)
The implementation of community service activities that will be carried out in the form of soft skill education development for vocational students at SMK Putera Jaya Batam in Batam City. Soft skill s education is very useful for vocational school graduates who will enter the world of work, with this ability it will make it easier for graduates to adapt to the work environment. Besides that, the soft skill competencies possessed by vocational school graduates will help in training a good work ethic and the ability to solve problems with any method and supported by a good leadership spirit, making it easier for graduates to work in a team. There are several soft skill s that need to be mastered by vocational school graduates including creative thinking skills, problem solving skills, interpersonal skills, intrapersonal skills, communication skills, leadership skills. From some of these abilities, an activity is made that is able to optimize the implementation of information technology-based soft skill s in academic education in vocational schools through community service activities by applying design thinking methods, leadership training and implementing simple applications commonly used by the community, with the hope that this activity is able to provide an overview of how to implement soft skill s in the world of work, and students also know the importance of soft skill s in the world of work so as to increase the interest of students to continue to explore and master soft skill s education as an answer to future challenges as quality vocational graduates